(untitled) (International relations and international law Journal, 2016)
Manufacture of ceramic products (including pottery) by medieval masters depended on many different factors, among them mainly from various climatic types, the presence of rich natural resources and the level of economic and cultural development of the population of this territory. Scientists, naturalists, travelers, poets, missionaries and researchers in their writings, diaries and reports give information on the active extraction of natural minerals by primitive facilities and their use in metallurgy and ceramic production of Northern Azerbaijan. To the intensive development of metallurgic and ceramic production in the cities of Northern Azerbaijan also contributed construction of furnaces from kaolin-fire clay with different impurities. S.M Gaziyev, O. Sh. Ismizadeh, V.G. Aliyev, G.M Ahmadov, G.A. Jiddy, F.A. Ibrahimov, K.M. Aliyev [1], A.B. Nuriyev , G.S. Ismailzadeh, M.M. Aliyev, M.A. Qashqai [2], T.I. Golubkina [3], G.G.Aghayev note that development of the required for pottery high-grade deposits of clay, quartzite and Iceland (field) spar which a lot in Northern Azerbaijan, began from the ancient times. Archaeological material undergone to chemical analysis is similar in mineralogical composition with the above-mentioned deposits. As is well known, traditional methods are created only where there is sufficient material required (7). Hightemperature thermal regime within the 700-1000C and more was achieved at the expense of the furnace with an open flame strong thrust that is the final stage of production of local pottery products, which were made on tastes of the population.